2021
DOI: 10.7717/peerj.12561
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection ofEnterococcusand vancomycin resistance using recombinase polymerase amplification

Abstract: Vancomycin-resistant enterococci (VRE), especially Enterococcus faecium, have been a global concern, often causing serious healthcare-associated infections. We established a rapid approach for detecting E. faecium and vancomycin-resistance genes (vanA and vanB) in clinical samples using isothermal recombinase polymerase amplification (RPA) combined with a lateral-flow (LF) strip. Specific RPA primer sets and probes for ddl (to identify the presence of E. faecium) vanA and vanB genes were designed. The RPA reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…However, preparation times for each step were not included. The RPA-LF assay also provided the limit of detection lower than those of the RPA-AGE and the conventional PCR-AGE method, similar to previous reports (10–100 times) [ 27 , 28 , 29 , 30 , 31 ]. To reduce the cost of the RPA-LF assay, the RPA reaction using the RPA reagents of TwistAmp™ Kit was performed in the small final volume of 12.5 µL as described previously [ 28 , 41 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, preparation times for each step were not included. The RPA-LF assay also provided the limit of detection lower than those of the RPA-AGE and the conventional PCR-AGE method, similar to previous reports (10–100 times) [ 27 , 28 , 29 , 30 , 31 ]. To reduce the cost of the RPA-LF assay, the RPA reaction using the RPA reagents of TwistAmp™ Kit was performed in the small final volume of 12.5 µL as described previously [ 28 , 41 ].…”
Section: Discussionsupporting
confidence: 87%
“…The RPA-LF assay is now widely applied to detect and identify antimicrobial resistance genes, such as mobilized colistin resistance-1 ( mcr-1 ) [ 26 ], macrolide efflux A ( mefA ) [ 27 ], methicillin resistance ( mecA ) [ 28 ], and extended-spectrum β-lactamase (ESBL) genes [ 29 ]. It was also successful to apply for rapid and direct detection of Staphylococcus aureus plus methicillin resistance as well as Enterococcus plus vancomycin resistance in positive blood cultures, suggesting the use of RPA-LF assay as a POC device [ 30 , 31 ]. The international patent for RPA primers of bla OXA-48-like by Sutton et al [ 36 ] was reported in 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Srirattakarn et al established RPA-LFS to monitor MRS, the sensitivity and specificity of RPA-LFS were 92.1% and 100% respectively (Srisrattakarn et al, 2020). RPA-LFS could also be used to detect vancomycinresistant enterococci (Panpru et al, 2021). Singpanomchai et al established an allele-specific RPA-SYBR amplification system to detect multidrug-resistant tuberculosis, this method designed specific primers for the alleles of four major mutations rpoB516, rpoB526, rpoB531, and katG315.…”
Section: The Application Of Rpa In Drug Resistance Gene Detectionmentioning
confidence: 99%
“…established RPA-LFS to monitor MRS, the sensitivity and specificity of RPA-LFS were 92.1% and 100% respectively ( Srisrattakarn et al., 2020 ). RPA-LFS could also be used to detect vancomycin-resistant enterococci ( Panpru et al., 2021 ). Singpanomchai et al.…”
Section: The Application Of Rpamentioning
confidence: 99%